Anti–cytotoxic T-lymphocyte–associated antigen-4 monoclonal antibody quavonlimab in combination with pembrolizumab: Safety and efficacy from a phase I study in previously treated extensive-stage small cell lung cancer. (September 2021) - Cho, Byoung Chul; Yoh, Kiyotaka; Perets, Ruth; Nagrial, Adnan; Spigel, David R.; Gutierrez, Martin; Kim, Dong-Wan; Kotasek, Dusan; Rasco, Drew; Niu, Jiaxin; Satouchi, Miyako; Ahn, Myung-Ju; et al.
Highlights: Anti-CTLA-4 antibody quavonlimab + pembrolizumab was assessed in extensive-stage SCLC. Encouraging antitumor activity was observed in patients with extensive-stage SCLC. The combination was tolerable with manageable toxicities. Abstract: Objectives: This first-in-human phase I study (NCT03179436) investigated anti–cytotoxic T-lymphocyte-associated protein 4 monoclonal antibody quavonlimab and anti–programmed death 1 monoclonal antibody pembrolizumab in patients with advanced solid tumors. The study was conducted in two parts: dose-escalation (part 1) and dose-confirmation (part 2). First-line treatment with quavonlimab + pembrolizumab conferred encouraging antitumor activity (objective response rate [ORR], 28%-40%) and was generally well tolerated (grade ≥ 3 treatment-related adverse events [TRAEs] were lowest with quavonlimab 25 mg every 6 weeks [Q6W] at 30% and highest with quavonlimab 75 mg Q3W at 57%) in non–small cell lung cancer. We present data from patients with extensive-stage small cell lung cancer (SCLC) receiving second-line or later therapy. Materials and Methods: Patients with stage III/IV SCLC received quavonlimab 75 mg Q6W plus pembrolizumab 200 mg Q3W for ≤ 2 years. Primary endpoints were safety and tolerability; ORRs as assessed by blinded independent central review per Response Evaluation Criteria In Solid Tumors v1.1 was a secondary endpoint. Progression-free survival (PFS), overall survival (OS), and the correlation of response with PD-L1 expression were exploratory endpoints. Results: Forty patients with extensive-stage SCLC received treatment; median follow-up was 13 months. Dose-limiting toxicity occurred in 4 patients (10%). TRAEs occurred in 80% of patients; grade 3 events occurred in 33% of patients and no grade 4/5 events were reported. Confirmed ORRs (95% CI) were 18% (7–33) among all patients, 7% (<1–34) for PD-L1–positive tumors ( n  = 14), and 19% (5–42) for PD-L1–negative tumors ( n  = 21). Response duration ranged from 2.9 to 19.1+ months. Median PFS was 2.0 months; 6-month PFS rate was 26%. Median OS was 11.0 months; 6-month OS rate was 66%. Conclusions: Encouraging antitumor activity was observed with quavonlimab + pembrolizumab in patients with extensive-stage SCLC; responses were observed in PD-L1–positive and PD-L1–negative tumors. The combination was tolerable with manageable toxicities.